PENGARUH KOMPENSASI DAN PROMOSI JABATAN TERHADAP KEPUASAN KERJA KARYAWAN PADA PT CERIA JUSINDO NUSANTARA JAKARTA - Cay, Sam; Sumiaty, Raden Yeti (RJABM (Research Journal of Accounting and Business Management), 2022)
This study aims to determine the effect of compensation and promotion on employee job satisfaction at PT Ceria Jusindo Nusantara Jakarta. The research hypothesis being tested is whether there is a significant effect between Compensation and Position Promotion on Employee Job Satisfaction at PT Ceria Jusindo Nusantara Jakarta. The research method used in this research is descriptive quantitative research method, the sampling method used is a saturated sample of 50 employees. The data collection technique is using a questionnaire, while the data analysis method used is validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient analysis (R), coefficient of determination analysis and hypothesis testing. Based on the results of the study using SPSS 25, the t-test results obtained that tcount for compensation is smaller than the ttable value of 0.564 or (0.575> 0.05) with a significant value of 0.575> 0.05. So it can be concluded that partially compensation has a positive but not significant effect on employee satisfaction. This means that Ho is accepted and Ha is rejected. The tcount value of work motivation is greater than ttable 1.677 or (3.869 > 1.677) with a significant value of 0.000 <0.05. So it can be concluded that partially promotion has a positive and significant effect on employee job satisfaction. This means that Ho is rejected and Ha is accepted. For the F test, the Fcount value is 30,839 and a significant value of 0.000 so that it can be concluded that compensation and promotion simultaneously have an effect on employee performance as evidenced by the Fcount 30.839 > Ftable 3.20 and a significant value of 0.000 <0.05, so it can be concluded that Ho is rejected and Ha accepted. The results of multiple linear analysis obtained Y = 8.057 + 0.063 X1 + 0.742 X2 Keywords: Compensation, Promotion and Employee Job Satisfaction.